Mortgage Debt Overhang: Reduced Investment by Homeowners at Risk of Default - MELZER, BRIAN T. (Journal of Finance, 2017)
ABSTRACT Homeowners at risk of default face a debt overhang that reduces their incentive to invest in their property: in expectation, some value created by investments in the property will go to the lender. This agency conflict affects housing investments. Homeowners at risk of default cut back substantially on home improvements and mortgage principal payments, even when they appear financially unconstrained. Meanwhile, they do not reduce spending on assets that they may retain in default, including home appliances, furniture, and vehicles. These findings highlight an important financial friction that has stifled housing investment since the Great Recession.